Phytochemical Assessment of The Extracts of Stem (Bark) and Leaves of Theobroma Cocoa Materials: Experimental Procedure and Its Comparison to Literature - Abulude, Francis Olawale; Ogunkoya, Mary Omofolarin; Adenibuyan, Grace Bamise; Arifalo, Kikelomo Mabinuola; Akinusotu, Akinyinka; Samuel, Ademola; Adamu, A.; Kenni, Amoke Monisola; Bello, Lateef Johnson (Bumi Publikasi Nusantara, 2022)
Plants had already long been utilized as medicines to treat illnesses. Theobroma cocoa is a plant with antifungal, antibacterial, antioxidant, antiemetic, larvicidal, hepatoprotective, anti-diarrheal, anti-inflammatory, antimalarial, anthelmintic, antiarthritic, wound healing, and anticarcinogenic potential. The purpose of this study was to look into the phytochemical compositions of crude extracts of Theobroma cocoa leaves and stem (bark) materials. Carbohydrates, saponins, and phlobatannins were found in higher concentrations in both the stem (bark) and the leaves, whereas tannins, glycosides, resins, and alkaloids were found in lower concentrations in both samples. Depending on the solvent used for extraction, different phytochemical compositions are obtained in each part of the tree. However, for the majority of the phytochemicals, water extraction yielded higher concentrations.